2020
DOI: 10.1002/adhm.201901582
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Polymer Coating of Sulfur Dioxide‐Releasing Nanosystem Augments Tumor Accumulation and Treatment Efficacy

Abstract: Multiple drug resistance (MDR) exhibited by cancer cells and low intratumor accumulation of chemotherapeutics are the main obstacles in cancer chemotherapy. Herein, the preparation of a redox‐responsive sulfur dioxide (SO2)‐releasing nanosystem, with high SO2‐loading capacity, aimed at improving the treatment efficacy of cancers exhibiting MDR is described. The multifunctional nanomedicine (MON‐DN@PCBMA‐DOX) is designed and constructed by coating mesoporous organosilica nanoparticles with a zwitterionic polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…PDDN showed effective anti-tumor activity, which indicated that the SO 2 -releasing polymer prodrug was efficient in tumor-killing. The anti-tumor mechanism of SO 2 may be ascribed to the oxidative properties of SO 2 as well as its ability to increase intracellular ROS, which induced the death of the tumor cells [ [25] , [26] , [27] , [28] , [29] ]. At an equivalent drug concentration, the order of the cytotoxicity of the tested formulations was as follows: PDDN-DOX > DOX > PDDN.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PDDN showed effective anti-tumor activity, which indicated that the SO 2 -releasing polymer prodrug was efficient in tumor-killing. The anti-tumor mechanism of SO 2 may be ascribed to the oxidative properties of SO 2 as well as its ability to increase intracellular ROS, which induced the death of the tumor cells [ [25] , [26] , [27] , [28] , [29] ]. At an equivalent drug concentration, the order of the cytotoxicity of the tested formulations was as follows: PDDN-DOX > DOX > PDDN.…”
Section: Resultsmentioning
confidence: 99%
“…Gas therapy refers to the use of gas molecules, such as hydrogen (H 2 ), hydrogen sulfide (H 2 S) and nitric oxide (NO), for treating diseases, which has been recognized as a promising “green treatment” for cancer therapy [ [22] , [23] , [24] , [25] , [26] ]. As a member of the gases family, sulfur dioxide (SO 2 ) has attracted much attention in inhibiting tumor growth in recent years [ [27] , [28] , [29] , [30] , [31] , [32] ]. To achieve controlled and targeted drug release, various stimuli-activated SO 2 -releasing nanoplatforms have been prepared for enhanced cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disulphide-linking shell was decomposed under GSH stimulation in HCC cells, causing release of NPQ ( O 2 -(2,4-dinitro-5-{[2-(β-d-galactopyranosyl olean-12-en-28-oate-3-yl)-oxy-2-oxoethyl] piperazine-1-yl}phenyl) 1-(methylethanolamino)diazen-1-ium-1,2-dilate) which subsequently decomposed into NO under catalysis of GSTπ. We developed mesoporous organosilica nanoparticles (MON) with a disulphide framework to load 2,4-dinitrobenzenesulphonylchloride (DN, a SO 2 prodrug) for GSH-responsive carrier degradation and SO 2 release [ 35 ]. Chen et al .…”
Section: Strategies For Engineering Stimuli-responsive Gas-releasing Nanomedicinesmentioning
confidence: 99%
“…Nowadays, mesoporous nanoparticles have attracted extensive interest because their high loading capacity is suitable for drug loading and delivery (Yao et al, 2017;Teng et al, 2018;Chen et al, 2019Chen et al, , 2020. Among these mesoporous materials, considerable attention has been paid to mesoporous organosilica nanocapsules (MONPs) since their excellent biocompatibility, large surface area, adjustable pore volume, and easily modified surface (Tao et al, 2018;Teng et al, 2018;Yao et al, 2020). MONPs are synthesized using organic group-bridged siloxanes as silicon sources, which is different from pure Si-O-Si groups of inorganic mesoporous silica nanoparticles (MSNs) (Chen et al, 2013;Teng et al, 2014b;Croissant et al, 2015).…”
Section: Introductionmentioning
confidence: 99%